ANALYSIS OF PRESIDENTIAL INAUGURAL ADDRESSES USING SEARLE'S TAXONOMY OF SPEECH ACTS - Paulus Widiatmoko (University of Kuningan, 2017)
This study analyzes the performance of Searle speech acts in presidential inaugural addresses. Five presidential inaugural addresses taken as the samples of this study were analyzed using Searles speech act taxonomy and different distinctive features of illocutionary acts. The findings of this study revealed the frequency and comparison of the speech act performance. Each inaugural address possessed distinctive characteristics influenced by sociopolitical, economic, and historical situation of the countries. In addition, some commonalities in relation to the performance of Searles speech act taxonomy were also observed.Keywords: speech acts, taxonomy, presidential inaugural address